Wireless Sensor Networks for Road Traffic Monitoring - Micek, Juraj; Karpis, Ondrej (Communications - Scientific letters of the University of Zilina, 2010)
The paper presents an analysis of communication technologies that should lead to choosing technology appropriate for road traffic monitoring. One of the best available communication technologies is standard ZigBee. Experimental measurements of data rate with respect to distance under different operating conditions are presented. Based on obtained results it is possible to say that using ZigBee technology in wireless sensor networks is appropriate if we expect lower data rates (70 kbps).